(untitled) (Journal of the College of Basic Education, 2025)
Andalusian poetry was known for the diversity of its meanings and poetic purposes, and poetry emerged as one of these purposes. The works of Professor Omar Ibrahim Tawfiq are the lens through which he looked at the political, social and cultural aspects of life in Andalusia, relying on the available sources in the various sciences that are related to the study, and the poets’ collections. Those whose names are mentioned in his books, in the book The Picture of the Andalusian Society in the Fifth Century of Migration (politically, socially and culturally), poetry reflected the different images of their lives about sincerity and interaction and was influenced by them in its images, methods, language, music and content. Andalusian, as for praise poems, they are a series of long poems started by a group of Andalusian poets, and due to the Andalusian need for rhythmic poems suitable for chanting and chanting, they tended to systems of poems that correspond to the remembrance councils or councils of the Prophet’s celebration. The research was a comprehensive study of the praise of the Prophet in Andalusia through careful investigation of the Andalusian sources and referring to the least The mother who was blessed with this topic, as for the ruling and preaching of Ibn Leon al-Tajibi, in his time the area of ​​wisdom poetry and sermons increased with the increase of strife and wars and the breaking of the thorn of the Islamic state, especially during the era of the kings of the sects when they were fighting among themselves, so a class of preaching poets appeared, the poetic experience of Ibn Leon’s passages is characterized With the elevation of the emotional, emotional and emotional tone with its human horizons, by virtue of the causes, issues and events that preoccupied Andalusia, and their effects were reflected on the human being, thought and vision, the lyrical passages were mixed with crying, grief, sorrow, bitterness, despair, determination, strength and patience in a molten rhetorical and preaching style.